IMPROVING STUDENTSâ COMPREHENSION OF POEMS USING TWO STAY-TWO STRAY STRATEGY - Hamiddin, Hamiddin (Vidya Karya Jurnal Kependidikan, 2012)
Abstract: The study is directed to improve studentsâ comprehension of poems using the Two Stay-TwoStray strategy. The subject of this study is 23 students of the sixth semester of English department ofFKIP at Islamic University of Malang. This study uses collaborative action research design which consistsof four main steps: planning, implementing, observing, and reflecting. The data is taken from quiz,observation checklist and field notes. The findings indicate that using TS-TS strategy can improve thestudentsâ comprehension of poems. The average score of studentsâ test in Cycle 2 is 80 and the studentsâactive involvement in Cycle 2 is 86%. The data are obtained from the implementation of TS-TS strategyin improving studentsâ comprehension of poems.Abstrak: Penelitian ini bertujuan untuk meningkatkan penguasaan siswa terhadap puisi denganmenggunakan strategi Two stay-Two Stray. Subjek penelitian adalah 23 orang mahasiswa semester 6Jurusan Pendidikan Bahasa Inggris FKIP Universitas Islam Malang. Penelitian ini menggunakan desainpenelitian tindakan kelas yang terdiri atas empat langkah utama, prencanaan, pelaksanaan, observasidan refleksi. Data diperoleh dengan menggunakan kuis, observasi dan catatan lapangan. Temuanpenelitian menunjukkan bahwa strategi TS-TS dapat menigkatkan penguasaan siswa terhadap puisi.Rata-rata skor siswa paa siklus 2 adalah 80 dan keterlibatan aktivitas siswa di siklus 2 adlah 86% .Data ini diperoleh dri implementasi strategi TS-TS dalam meningkatkan penguasaan siswa terhadappuisi.Key Words: comprehension of poems, Two Stay-Two Stray Strategy